Transformasi Komunikasi Pembangunan Perempuan dalam Mempersuasi Pertumbuhan Ekonomi Mikro Melalui Industri Batik Pekalongan - Mukoyimah; Hadi Subhan (IQTIDA : Journal of Da'wah and Communication, 2025)
This study aims to examine the role of women's communication in stimulating microeconomic growth in the batik-producing area of Pekalongan. The research employs a qualitative field approach with a focus on public communication. Primary data were collected through interviews with female batik workers from home industries to factories, using snowball sampling to identify informants based on predefined indicators. The data were then filtered through the lens of development communication and documented accordingly. Data analysis followed the stages of data collection, reduction, presentation, and conclusion drawing. The findings indicate that women play a significant role in improving the standard of living in Pekalongan. This is reflected in the regional income growth, which increased from 3.59% in 2021 to 5.76% in 2022. Women's participation takes various forms, such as selling batik through digital platforms, contributing to batik design and sewing, and sharing their skills with others in the community. These activities not only enhance their craftsmanship but also support household income and contribute to regional economic development. Additionally, informal knowledge-sharing among neighborhoods fosters financial independence and specialized skills among women. Overall, women's communication practices in the batik industry demonstrate strong potential in driving sustainable local economic empowerment.